2023
DOI: 10.3390/molecules28166116
|View full text |Cite
|
Sign up to set email alerts
|

Three Iodoargentate-Based Hybrids Decorated by Metal Complexes: Structures, Optical/Photoelectric Properties and Theoretical Studies

Minghui Liu,
Xiaochen Ren,
Weiyang Wen
et al.

Abstract: So far, the development of new iodoargentate-based hybrids, especially those compounds with metal complex cations, and the understanding of their structure–activity relationships have been of vital importance but full of challenges. Herein, using the in-situ-generated metal complex cations as structural directing agents, three new iodoargentate-based hybrids, namely, [Co(phen)3]Ag2PbI6 (phen = 1,10-phenanthroline; 1), [Ni(5,5-dmpy)3]Ag7I9·CH3CN (5,5-dmpy = 5,5-dimethyl-2,2-bipyridine; 2) and [Co(5,5-dmpy)3]Ag5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This is markedly different from some iodoplumbate-based hybrid materials (e.g., [CH 3 NH 3 ]PbI 3 ), which usually performed poorly due to the long-term instabilities [38]. Under the visible light condition, the average photocurrent density reached to 0.37 µA•cm −2 (Figure 5a), which is comparable to those of some highly reactive iodoargentate-based hybrids, such as AgI(bpt), Ag 2 I 2 (phen), [Co(5,5-dmpy) 3 ]Ag 5 I 8 , [La(dpdo)(DMF) 14 ]Ag 12 I 18 (dpdo = 4,4 ′ -bipyridine N,N'-dioxide) and [Co(bipy) 3 ] 2 Ag 4 Bi 2 I 16 [21,29,35,39]. Moreover, the on/off current density of compound [H 2 -4,4 ′ -dpa]Ag 6 I 8 could be further enhanced by exposing the designed photoelectrode to the full-spectrum circumstance, with the observed photocurrent density of 1.23 µA•cm −2 (Figure 5b).…”
Section: Photoelectric Performances Of Compoundmentioning
confidence: 69%
See 1 more Smart Citation
“…This is markedly different from some iodoplumbate-based hybrid materials (e.g., [CH 3 NH 3 ]PbI 3 ), which usually performed poorly due to the long-term instabilities [38]. Under the visible light condition, the average photocurrent density reached to 0.37 µA•cm −2 (Figure 5a), which is comparable to those of some highly reactive iodoargentate-based hybrids, such as AgI(bpt), Ag 2 I 2 (phen), [Co(5,5-dmpy) 3 ]Ag 5 I 8 , [La(dpdo)(DMF) 14 ]Ag 12 I 18 (dpdo = 4,4 ′ -bipyridine N,N'-dioxide) and [Co(bipy) 3 ] 2 Ag 4 Bi 2 I 16 [21,29,35,39]. Moreover, the on/off current density of compound [H 2 -4,4 ′ -dpa]Ag 6 I 8 could be further enhanced by exposing the designed photoelectrode to the full-spectrum circumstance, with the observed photocurrent density of 1.23 µA•cm −2 (Figure 5b).…”
Section: Photoelectric Performances Of Compoundmentioning
confidence: 69%
“…Of note, all atoms in compound 1 are located in the 4e site with one site symmetry. In the [Ag 6 I 8 ] n 2n− anionic moiety, all Ag centers adopted the tetrahedral geometries (Figure 1b), with the relevant Ag−I distances of 2.648( 8 -dimethyl-2,2 ′bipyridine) [3,5,8,12,17,20,21]. As for the I atoms, three different coordination modes exist: I(3) and I(6) atoms act as the bridging fashions; I(2), I(4), I(7) and I(8) atoms take on the µ 3 -I styles; while the I(1) and I(5) atoms are µ 4 -I manners connecting four Ag + ions.…”
Section: Structural Description Of Compoundmentioning
confidence: 99%
“…5a). 34–37,41–45 This high value also suggested that compound 1 possessed good carrier transport and separation ability, which is a critical prerequisite for an excellent photoconductive material. Predominantly, its “on/off” switching ratio could be further enhanced when exposed to a full-spectrum light environment, with an achieved photocurrent density of 1.10 μA cm −2 (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…This phenomenon is normal and commonly observed in some halogen-abundant haloargentate hybrids, such as [NH 4 ][Fe(bipy) 3 ] 2 Ag 6 Br 11 , [Co(bipy) 3 ] 2 Ag 4 Bi 2 Br 16 , [Fe(bipy) 3 ]AgBiBr 6 , [Co(5,5-dmpy) 3 ]Ag 5 I 8 , and [Zn(phen) 3 ] 2 Ag 2 Bi 2 I 12 . 16,34–37 The relative contributions of various intermolecular contacts to the Hirshfeld surface are summarized in Fig. 3d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation